PENGEMBANGAN E-MODUL BERBASIS WEB APLIKASI PADA MATERI GELOMBANG KELAS XI - Bahri, Syaiful; Rosa, Friska Octavia; Alarifin, Dedy Hidayatullah; Prihandono, Eko (Universitas Muhammadiyah Metro, 2022)
Abstract: This study aims to determine the design of web-based e-module applications in physics learning, the feasibility level of web-based e-module applications in physics learning, and the effectiveness of web-based e-module applications in increasing students' learning motivation. This development uses the ADDIE development model. This research was conducted at SMA NEGERI 5 METRO in April 2022. The data collection instrument used in the research on the development of this web-based e-module was in the form of an expert validation questionnaire and a student response questionnaire as the effectiveness of the web-based e-module media application Data analysis techniques used in this study is an analytical technique related to the purpose of this research, so that data analysis is carried out on media design, media feasibility and the level of media effectiveness on students' learning motivation, so that researchers can easily understand the data and draw conclusions. Based on the results of the e-module feasibility test of material and media experts, through expert validation and student response trials, an average percentage value of 82.45% was obtained in the very feasible category. Based on data from learning motivation, an average value of 82.16% was obtained so that in measuring student motivation using web-based e-modules this application was successful.Keywords: E-Module, Google Sites, Learning Motivation